The story of beautiful girl - Simon, Rachel, 1959- (New York, N.Y. : Grand Central Publishing/Hachette Book Group, 2011)
A novel about a woman who can't speak, a man who is deaf, and a widow who finds herself suddenly caring for a newborn baby.
Keywords: Large type books; People with disabilities -- Fiction